2018
DOI: 10.1097/md.0000000000013306
|View full text |Cite
|
Sign up to set email alerts
|

Corneal power changes with Scheimpflug rotating camera after hyperopic LASIK

Abstract: To evaluate surgically induced refractive change (SIRC) by manifest refraction and corneal power changes using an automated keratometer and Scheimpflug rotating camera, and to find the best keratometric measurements reflecting SIRC after hyperopic laser-assisted in situ keratomileusis (LASIK).This retrospective study included 18 eyes of 18 patients undergoing hyperopic LASIK using the Schwind Amaris 750S excimer laser. All measurements were performed preoperatively and 12 months postoperatively. Cycloplegic ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
0
5
0
1
Order By: Relevance
“… 2 , 27 , 28 Whang et al preferred centration over the apex, given that the center of the pupil may change as the pupil changes shape. 19 Qian et al 8 and Savini et al 10 opted for centration over the pupil. Naeser et al found there to be no significant difference in centration over pupil or apex.…”
Section: Discussionmentioning
confidence: 99%
“… 2 , 27 , 28 Whang et al preferred centration over the apex, given that the center of the pupil may change as the pupil changes shape. 19 Qian et al 8 and Savini et al 10 opted for centration over the pupil. Naeser et al found there to be no significant difference in centration over pupil or apex.…”
Section: Discussionmentioning
confidence: 99%
“…All of them have come to the conclusion that TCRP is more suitable for actual refractive changes than only analyzing the axial refractive power of corneal surface [ 12 , 14 ]. In hyperopic LASIK [ 14 , 15 ], the TCRP 4.0 mm/5.0 mm zone calculation was proved to best predicted the surgically induced change in manifest refraction. Though their comparison standard is sphere equivalent change, not CHM in present study.…”
Section: Discussionmentioning
confidence: 99%
“…Different from myopia, hyperopia is corrected by increasing the central refractive power and reducing the peripheral refractive power. There are a few studies about cornea power change after hyperopic surgery, and most of them focused on hyperopic LASIK [11,[14][15][16][17]. Hyperopic LASIK used excimer laser to ablate midperiphery cornea area.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the TNP and TCRP (total corneal refractive power) have attracted greater attention because they take into account the true refractive index of the anterior and posterior surface curvature and the directly measured radius of the posterior surface curvature. In contrast, TCRP also reflects the true corneal thickness and corneal asphericity value [27,28]. The difference between TNP and simK lies only in the true refractive indexes of the anterior and posterior surfaces of the cornea and the posterior surface curvature radius.…”
Section: Relationship Between the B/f Ratio And Refractive Powermentioning
confidence: 99%